2019
DOI: 10.1111/ajo.13059
|View full text |Cite
|
Sign up to set email alerts
|

Unmet treatment needs in patients with chronic pelvic pain in a New Zealand gynaecology service

Abstract: BACKGROUNDChronic pelvic pain (CPP) is defined as continuous or intermittent pain in the abdomen and/or pelvis lasting for at least six months. 1 Current prevalence estimates suggest one in every four to six women experience CPP, making it relatively common. 2,3 For many of these women, CPP is accompanied by high levels of distress, disability, and reduced quality of life. 2,3 The high levels of distress experienced by these women have resulted in strong lobbying for increased treatments to alleviate CPP. 2 Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
(122 reference statements)
0
7
0
Order By: Relevance
“…These include practitioner bias, logistical, and financial barriers 36 , as well as significant inequities, with ethnic minorities experiencing poorer health outcomes 38 – 40 . For CPP sufferers, the current healthcare model is inadequate, highlighting a specific area of unmet patient need 41 . Furthermore, an extensive body of international literature shows that the culture of normalising CPP may contribute to diagnostic delay, and this normalisation effect may occur both informally and formally when patients are seen by a doctor 42 , 43 .…”
Section: Discussionmentioning
confidence: 99%
“…These include practitioner bias, logistical, and financial barriers 36 , as well as significant inequities, with ethnic minorities experiencing poorer health outcomes 38 – 40 . For CPP sufferers, the current healthcare model is inadequate, highlighting a specific area of unmet patient need 41 . Furthermore, an extensive body of international literature shows that the culture of normalising CPP may contribute to diagnostic delay, and this normalisation effect may occur both informally and formally when patients are seen by a doctor 42 , 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The psychological profiles of people with endometriosis and pelvic pain presenting to a multidisciplinary clinic have been highlighted in seven studies 20–26 . Bryant et al reported higher levels of anxiety symptoms compared to depressive symptoms in patients with chronic pelvic pain, which was strongly correlated with pain catastrophising and weaker self‐efficacy 20 .…”
Section: Resultsmentioning
confidence: 99%
“…Several critical methodological issues should be considered in interpreting the results of this study. First, we recognise that some studies focused on pelvic pain as the primary health concern, and while endometriosis was mentioned in these papers, it was not the main focus of the work 11–14, 19–21,23 . As chronic pelvic pain can occur in the absence of endometriosis (or continue following successful treatment of endometriosis), our study set may be diluted by non‐endometriosis‐specific findings.…”
Section: Discussionmentioning
confidence: 99%
“…21 An audit of attendees to the CWH gynaecology clinic with pelvic pain found a strikingly high level of catastrophic worry about pain and other psychosocial yellow flags. 22 Surgical intervention is unlikely to improve these factors. There is, however, evidence that multidisciplinary (MDT) pain clinics where interventions address such psychosocial domains improve quality of life and reduce healthcare costs by over 90% for those living with musculoskeletal pain.…”
Section: Discussionmentioning
confidence: 99%